The isolation of cloned cDNA sequences which are differentially expressed in human lymphocytes and fibroblasts. - Crampton, J (1980)
Poly(A)+ RNA populations derived from normal lymphocytes and fibroblasts have been compared by hybridising each RNA to cDNA derived from the other RNA population. This indicated that approximately 75% of the sequences were common to both, and that these were present at different concentrations in the two cell types. The two RNA populations were further compared by hybridising them to a cDNA recombinant library derived from lymphocyte poly(A)+ RNA. This allowed the identification of clones containing sequences which are abundant in lymphocyte poly(A)+ RNA but absent or rare in fibroblast poly(A)+ RNA. A direct estimation of the abundance of five of these sequences in lymphocyte cDNA demonstrated that clones can be detected by such a procedure if they represent 0.2% or greater of the original cDNA population.